"Air-Assisted" Donor Lenticule Insertion in Descemet Stripping Endothelial Keratoplasty in Aphakia With Large Iris Defect and Without Posterior Capsular Support. Issue 7 (13th July 2022) - Basak, Soham; Basak, Samar K.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Purpose: The purpose of this study was to report a novel technique of donor lenticule insertion in Descemet stripping endothelial keratoplasty (DSEK) in aphakic corneal edema with large iris defect and without any posterior capsular support. Methods: This was a retrospective consecutive interventional case series. Clinical records of ten 1-eyed aphakic patients with corneal edema with large iris defect and no capsular support who underwent air-assisted donor lenticule insertion in DSEK were evaluated. After making 6.0- to 6.5-mm sclerocorneal tunnel and 2 side ports, limited anterior vitrectomy was performed if required. Then, Descemetorhexis was performed under air through side ports. Manually dissected donor lenticule was inserted into the anterior chamber under full-chamber air by a 30-G needle push-in technique. Further air tamponade was given if necessary. No fluid–air exchange was performed. The patient was kept on the same operating table for at least 1 hour and then shifted. Graft attachments in early postoperative period, corrected distant visual acuity, and endothelial cell density after 3, 6, and 12 months were analyzed. Results: The mean postoperative follow-up period was 19.2 ± 6.7 months. There was no donor dislocation in this small group. All patients achieved a corrected distant visual acuity of 0.70 (20/100) after 3 months and maintained until 12 months. The endothelial cell density at 3 months (n = 8) was 2028 ± 151/mm 2, at 6 months (n = 7) 1776 ± 198/mm 2, and at 12 months (n = 7) 1721 ± 172/mm 2 . The corresponding endothelial cell loss was 25.8% ± 5.6%, 34.4% ± 5.1%, and 37.8% ± 7.1%, respectively. One graft failed after 15 months. Conclusions: "Air-assisted" donor lenticule insertion in DSEK is a safe surgical technique in aphakic patients with corneal edema with large iris defect and no capsular support.